Financing Supply of Islamic Banking During COVID-19 Outbreak in Indonesia - Muhammad Anif Afandi (Journal of Islamic Economic and Business Research, 2021)
This study aims to analyze the factors that affect the financing supply of Islamic banking during pandemic COVID-19 outbreak in Indonesia. The variable of financial performances of Islamic banking such as Return on Assets (ROA), Capital Adequacy Ratio (CAR), Financing to Deposit Ratio (FDR) and Non-Performing Financing (NPF) are used as the independent variables. Meanwhile, the impact of COVID-19 pandemic is analyzed using dummy variable. Furthermore, each of the independent variables and the dummy variable are tested its influence to the dependent variable, namely the financing supply of Islamic banking by using a proxy of the total financing. Ordinary Least Square (OLS) with double log model used as a data analysis technique with the results of the study show that the variable of ROA has a positive but not significant effect to the financing supply. Variable CAR and FDR each shows a negative and not significant effect to the financing supply. Whereas, the variable of NPF shows a negative and significant effect to the financing supply. Meanwhile, COVID-19 pandemic contributes in giving a positive and significant difference effect to the financing supply than before the presence of COVID-19 in Indonesia. The results of this study prove that the phenomenon of credit crunch in Islamic banking relative can be addressed during pandemic COVID-19 outbreak in Indonesia.